Incompatibility of the Concept of Culture Used in the Project of Interculturality with the Teaching of the Church - Pawlik, Jacek Jan (Studia Warmińskie, 2021)
The article focuses on the concept of culture in the teaching of the Church and of the project of interculturality. The difference between these discourses lies mainly in the understanding of values. Adopting absolute truth from a religious perspective opposes the relativization of the norm in the intercultural project. Although both approaches are compatible with the need for a harmonious life in a multicultural society, the proposed ways of implementing this task differ fundamentally. John Paul II calls for the creation of a „civilization of love” based on the ideals, and an intercultural project, for building a society on the basis of consequentialism.